Balanced Nutrition Education with Animated Video Media and Smart Plate Practice on Increasing Knowledge of Students of SMPN 3 Hamparan Perak - Riana Fraulein Simamora; Bina Melvia Girsang (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Adolescence is the period when nutritional problems are most likely to occur because the growth and development of the body accelerates and requires more energy. In addition, adolescents prefer to follow changes in lifestyle and diet that are not necessarily healthy, causing various nutritional problems. Objective: This education is carried out to encourage students to make positive knowledge changes in accordance with a balanced diet during adolescence. Educational activities were carried out in the classroom which were attended by 60 students of class VIII of SMPN 3 Hamparan Perak. Method: The DS-23 Thematic Real Work Lecture (KKN-T) team conducted ice breaking, namely singing and headbanz games to raise students' enthusiasm. Giving a pre-test containing an assessment of knowledge about balanced nutrition. Then play an animated video, explain the material of balanced nutrition in adolescents which includes 4 pillars of balanced nutrition, calculation of body mass index, demonstration of filling the contents of my plate with appropriate innovation of smart nutrition plates. Questions and answers to ensure student understanding. At the end of the session, the team gave a post test and distributed snacks in the form of honey. Result: The results of the education showed an increase in the knowledge of class VIII students about balanced nutrition, especially in their teenage years. Conclusion: Students understand the concept of nutrition and know how to fill my plate in one meal so that it makes them more concerned about the intake that is eaten should not be less or more in order to avoid nutritional problems is one of the achievements expected by the team.